Designing a Responsive e-Learning Infrastructure: Systemic Change in Higher Education. Issue 1 (2nd January 2017) - Chow, Anthony S.; Croxton, Rebecca A.
ABSTRACT: As university administrators respond to increasing demands of the educational market to offer greater opportunities for online learning, their capacity to create an economically stable, sustainable, yet rich teaching and learning environment deserves immediate and continued attention. A university-wide study involving 130 participants examined the e-learning perceptions and needs of faculty, students, and staff as part of a needs assessment of the e-learning unit. Results suggest that faculty recognize the importance of e-learning, that students covet it for its convenience, and that real-time technology support was the top priority. Both the school and university resources, however, are not well aligned to meet these needs and remain largely separate and unintegrated. Implications suggest a need to increase the overall ease of use for the adoption of e-learning as a new technology for teaching and learning of both faculty and students and more closely aligned department and university resources.